Development of a Semi-Analytical Type Curve of Transient Pressure Response in Complex Well-Reservoir Architectures - Saeb Salih, Ibrahim; Ali Baker, Hussain (Iraqi Journal of Chemical and Petroleum Engineering, 2019)
The objective of the conventional well testing technique is to evaluate well- reservoir interaction through determining the flow capacity and well potential on a short-term basis by relying on the transient pressure response methodology. The well testing analysis is a major input to the reservoir simulation model to validate the near wellbore characteristics and update the variables that are normally function of time such as skin, permeability and productivity multipliers.Well test analysis models are normally built on analytical approaches with fundamental physical of homogenous media with line source solution. Many developments in the last decade were made to increase the resolution of transient response derivation to meet the complexity of well and flow media.   Semi-analytical modeling for the pressure transient response in complex well architecture and complex reservoirs were adopted in this research. The semi analytical solution was based on coupling the boundary condition of source function to the well segment. Coupling well-reservoir on sliced based technique was used to re-produce homogenous isotropic media from several source functions of different properties. The approach can model different well geometries penetrated complex reservoirs. A computer package was prepared to model the pressure transient response of horizontal, dual-lateral, multi-lateral wells in complex anisotropic reservoirs, multilayered, compartmentalized, system of various boundary conditions such as: bottom support aquifers, edge supported, gas caps, interference of injection. The validity of the proposed model was successfully checked by using the commercial simulator.